2010
DOI: 10.1111/j.1439-0426.2010.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and development of spines over the skin surface of the river puffer Takifugu obscurus (Tetraodontidae, Teleostei) during larval growth

Abstract: The histological structure and development of spines on the skin surface of Takifugu obscurus were studied during larval development conducted artificially with an average 30& salinity and 18.0-20.3°C water temperature. The epidermis comprises an outermost layer, middle layer, and the stratum germinativum, and contains three types of gland cells: small spherical or flask-shaped mucous cells, larger sacciform mucous cells, and large granular cells. The dermis and subcutis follow. The spines first appear over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…The mineralized structure is in the shape of a hollow cone, and the tip of the cone is elongated to form a compact thorn ( Figure 2D). This structure is similar to those described in other pufferfish species [16,28,44,45]. crosses of T. niphobles, T. pardalis, and T. snyderi.…”
Section: Developmental Pattern Of Spiny Scalessupporting
confidence: 86%
“…The mineralized structure is in the shape of a hollow cone, and the tip of the cone is elongated to form a compact thorn ( Figure 2D). This structure is similar to those described in other pufferfish species [16,28,44,45]. crosses of T. niphobles, T. pardalis, and T. snyderi.…”
Section: Developmental Pattern Of Spiny Scalessupporting
confidence: 86%
“…In addition to inflating their bodies, porcupine fish also have long spines across their body that are erectile when the fish inflates [26]. These spines serve to increase the effective volume of the porcupine fish, making it harder for predators to swallow, and are actually modified scales [26,41,42].…”
Section: Spinesmentioning
confidence: 99%
“…Hertwig, et al [43] observed that the dermal spines inTetraodon steindachneri have bilateral symmetry and have a laminated longitudinal cross-section. The spines of the T. steindachneri and Takifugu obscurus can be stained using alizarin red-S ( Figure 5), a histological dye that indicates the presence of calcium [41,43]. Of note, spines have a dense outer layer of collagen around the mineralized core [43], as well as many concentric circles in the transverse cross-section of the spines [41].…”
Section: Spinesmentioning
confidence: 99%
See 1 more Smart Citation
“…지금까지 황복에 대한 연구는 생식생물학 (Jang 환경생리 et al, 1999a;Jang et al, 1999b), (Kim et 발생 al., 1996;Kim et al, 1997), (Jang et al, 초 1996;Yang & Chen, 2005;Byeon et al, 2011), 기 사육 세포유전학 (Kang et al, 2004), (Park et …”
Section: 양식방법이 개발되어 생산량 증가로 양식산 황복unclassified